On Equivocation and Failure in Anthropology. On the concept of «controlled equivocation» in Viveiros de Castro (Nóema, 2017)
The purpose of this article is to explore the concepts of «failure» and «equivocation» in cultural anthropology. Firstly, through the re-reading of The Effectiveness of Symbols by Claude Lévi-Strauss, it will be shown how a failure works through the epistemological entanglements between the anthropologist, his source/informant, and his academical «speech community». Secondly, the analysis of the method of «controlled equivocation» as elaborated by Eduardo Viveiros de Castro will introduce us to the centrality of translation in the discipline. The epistemological equivocation and the intra-and extra-cultural misunderstanding are the basis of the relation tout court, whatever that may be. Through the analysis of Amerindian Perspectivism we will show how, in recent years, the ethico-political awareness of cultural anthropology has radicalized and how the concept of equivocation can counterbalance the side effects of the epistemological representationalism.
Keywords: Failure; Ontological turn; Controlled equivocation; Viveiros de Castro; cultural translation